2016
DOI: 10.1016/j.jpowsour.2016.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic and photoelectrochemical activities of reduced TiO2−x/BiOCl heterojunctions

Abstract: A key issue to design highly efficient photoelectrodes for hydrogen production is how to prohibit the rapid carrier recombination. In order to use the visible light and reduce the recombination of electrons and holes, reduced TiO 2-x /BiOCl heterojunctions are successfully synthesized and the photoelectrodes are assembled in this work. The effects of various Bi/Ti molar ratios on the structural, morphological, optical, photoelectrochemical and photocatalytic activities of the resultant samples are investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…2b includes two peaks located at 164.5 eV and 159.2 eV that are corresponding to Bi 4 f 5/2 and Bi 4 f 7/2 . The band difference between Bi 4 f 5/2 and Bi 4 f 7/2 is 5.3 eV and the area ratio of both peaks is 4/3, which is in good accordance with the oxidation state of bismuth cations Bi 3+ [25,26]. Correspondingly, two peaks centered at 163.9 eV and 158.6 eV in sample Bi-230°C stay on the relatively low filed in comparison to those in sample Bi-270°C [27,28], probably attributing to the interaction of these species with metallic Bi in sample Bi-230°C at positions of 162.1 eV and 156.7 eV resulted from the electrons migrated from metallic Bi to bismuth oxide [23].…”
Section: Xrd Patterns and Xps Analysessupporting
confidence: 72%
See 1 more Smart Citation
“…2b includes two peaks located at 164.5 eV and 159.2 eV that are corresponding to Bi 4 f 5/2 and Bi 4 f 7/2 . The band difference between Bi 4 f 5/2 and Bi 4 f 7/2 is 5.3 eV and the area ratio of both peaks is 4/3, which is in good accordance with the oxidation state of bismuth cations Bi 3+ [25,26]. Correspondingly, two peaks centered at 163.9 eV and 158.6 eV in sample Bi-230°C stay on the relatively low filed in comparison to those in sample Bi-270°C [27,28], probably attributing to the interaction of these species with metallic Bi in sample Bi-230°C at positions of 162.1 eV and 156.7 eV resulted from the electrons migrated from metallic Bi to bismuth oxide [23].…”
Section: Xrd Patterns and Xps Analysessupporting
confidence: 72%
“…In addition, Fig. S2b shows both peaks of O1s at 530.4 eV and 529.3 eV in spectra of sample Bi-230°C and Bi-270°C argon etching with the 7 nm depth, characteristic of oxygen species adsorbed on the surface of sample during samples treatment and lattice oxygen in Bi-O bonds [25].…”
Section: Xrd Patterns and Xps Analysesmentioning
confidence: 98%
“…When CoWO 4 nanoparticles were coupled with BiOBr, the exchange of electrons and holes could occur at the two‐phase interface of the composite. The energy band alignment of CoWO 4 and BiOBr brings about the creation of a diffusion potential . When the BiOBr–CoWO 4 nanocomposite is illuminated by visible light, only CoWO 4 nanoparticles can absorb the radiation because the experimental E g value of CoWO 4 nanoparticles is narrower than that of BiOBr particles.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, reducing TiO 2 to create the self-dopants, including O and Ti 3+ defects, becomes interesting for increasing the photocatalytic activity and making use of the visible light. It was also shown that the combination of Ti 3+ self-doped TiO 2 with other materials, such as BiOCl, can effectively increase the photocatalytic activity …”
Section: Introductionmentioning
confidence: 99%